Like men working: feminine labor participation with marks of inequality of sort in agroindustria citrícola of the province of Tucumán, Argentina - Vazquez Laba, Vanesa (Universidade Estadual de Campinas, UNICAMP, Unidade da Faculdade de Ciências Aplicadas de Limeira-SP, vinculada ao Laboratório de Estudos do Setor Público, LESP, 2009)
The present feminista academic production has developed an ample repertoire of empirical investigations around knowing on the roots and the different formats from subordination of the women in the contemporary capitalist societies. The article tries to give account how although the women get up themselves like wageearning in an agro-industrial activity, modern, with exporting profile and which it creates feminine jobs, the labor bonds and the conditions of work are crossed by a masculine labor model that returns to generate inequality between the sort in the labor scope. The case study has been the citrícola agro-industrial activity, located in the province of Tucumán, Argentina.